Understanding the role of oxidation in bonding of aluminium alloys - Wu, G (2014)
The main aim of this work is to study the bonding behaviour of Al alloys as a function of temperature, time and processing conditions from a perspective of oxidation so as to gain a comprehensive knowledge of the oxidation issues during processing and to design better bonding approaches for different alloy systems. Two major parts of work have been carried out during the study: (a) the use of a stacking approach and a double pouring approach to potentially join two Al alloys and their effectiveness are assessed; and (b) a precise investigation of the oxidation mechanisms for Al-Cu and Al-Mg alloys using a combination of theoretical analysis and experimental characterization. The project started with the use of a stacking approach to try to bond two stacked Al alloys. The stacked sample can be viewed as a bi-metal which has an oxide bi-film layer at the bond interface. It was found that the bi-film layer was a physical barrier preventing direct metallic bonding. How this bi-film layer evolves during the bonding process was then investigated. The work then moved on to investigate the oxidation mechanisms of Al-Cu alloys and Al-Mg alloys in greater detail. The thermodynamics, kinetics of oxidation, chemistry and morphology of the oxide scale were particularly studied. Briefly speaking, in the case of the Al-Cu-O2 system, the oxidation proceeds in the order of amorphous γ-Al2O3 - to - crystalline γ-Al2O3 - to - α-Al2O3; in the case of the Al-Mg-O2 system, the oxidation proceeds as amorphous γ-Al2O3 to MgO to MgAl2O4 and the morphology of the oxide scale develops from a protective layer to a porously structured composite layer. A double pouring approach was finally developed to bond Al and Al-5Cu but the method has still not been perfected due to the formation of bi-film defects along the bond interface. Induction melting, squeeze casting, and extrusion bonding were therefore studied as an attempt to reduce the harmful effect of bi-film defects. Although all of the approaches exhibit some limitations, they have potential for future development.